The value relevance of SASB-based materiality disclosure: Evidence from Indonesian listed firms - Prayoga, Hadiyan; Soko, Felicyta Adelanam; Badruzaman, Jajang (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: ISSB issued IFRS S1 and S2 reporting that influence entities to disclose information about risks and opportunities based on SASB standards. This study examine whether materiality disclosure reflects on value relevance information content. The materiality item relates to the general purpose of financial reporting, helping users make decisions.Design/Methodology/Approach: Using regression analysis, this study analyse 330 firm-year observations from 71 firms listed on the Indonesia Stock Exchange from 2017-2022.Research findings: This study find positive relationship between materiality disclosure and value relevance information. In addition, firms with high materiality not accurately reflects on stock price related sustainability item.Theoretical contribution/Originality: This study provides novel evidence that materiality disclosure enhances value relevance by influencing stock prices. It extends the decision-usefulness perspective by showing that market responses to materiality vary across firms, highlighting the role of sustainability disclosure in shaping investors’ valuation.Practitioner/Policy implication: This study suggest that materiality disclosure serves as a strategic tool for firms to enhance market value, not just a compliance exercise. For regulators, the evidence supports ISSB’s mandate that materiality reporting is essential to provide decision-useful sustainability information for investors.Research limitation/Implication: First, this study is limited to the Indonesian context. Future research is encouraged to broaden the scope by including other countries, particularly those that are members of the IASB. Second, the study does not account for the issue of endogeneity within its methodological approach.